Digital Literacy of Pre-service Teachers in the Period Time of COVID-19 Pandemic - Veena Prachagool; Prasart Nuangchalerm; Parinda Yawongsa (Journal of Educational Issues, 2024)
Digital literacy is an important thing for modern pre-service teachers, they are key element to deal with technology for education and motivate classroom with effective infortion technology. This study aims to explore digital literacy of pre-service teachers during time of COVID-19 pandemic. The respondents were 54 pre-service teachers, rated the digital literacy based on the framework of teacher digital literacy, which consisted of 5 components: (1) social responsibility, (2) team-based learning, (3) information management, (4) processing and information presentation, and (5) digital integrity. Result revealed that the level of digital literacy of pre-service teachers is at high level in all components. It indicated that they are ready to deal with technology for education, but digital literacy is still engaged into them and in-service science teachers.